TOWARDS COMPREHENSIBILITY IN THE TRANSLATION OF GERMAN AND POLISH COURT NAMES - BIELAWSKI, Paweł (Comparative Legilinguistics, 2019)
The focus of this paper is centered on the translation of German and Polish court names. Based on a thorough analysis of the translation terms used in legal literature and dictionaries, the author concludes that the court names are often being translated in a way that makes it impossible for the reader to correctly identify the institution in question, thus undermining the comprehensibility of the target texts significantly. Pointing to the differences between the court systems of Germany and Poland, the author contemplates whether the dissimilarities between two institutions from different legal systems need always to be marked in the translation. On the basis of the comparative law theory, the meaning features essential for both legal communication and legal translation are identified and presented. In the next part, the author examines how to translate the court names so that the institution at issue is instantly recognizable in the target text. As a result, three comprehensive translation techniques are proposed. The presented translation techniques shall contribute to improving the comprehensibility of legal texts, and constitute an alternative to the descriptive translation of these institutions.